Handling students mental health during MCO - Murniati, Abu Karim (The New Straits Times Press (M) Bhd., 2020)
The closure of higher learning institutions and the abrupt shift towards online learning, combined with the admonition to stay put may hit students hard, especially those who are stuck in the university premises.